The impact of sustainable development on the relevance of accounting information and financial activities: Evidence from Thailand. - Mongkhol Moolkham (PLoS ONE)
This study investigates the impact of sustainable development on the relevance of accounting information and financial activities of companies listed on the Stock Exchange of Thailand (SET). The results reveal that earnings per share and book value per share have a positive effect on market value, implying that higher earnings signal strong financial performance, thereby attracting more investor interest. Short-term and long-term debt financing have a negative effect on market value, suggesting that debt financing leads to increased financial risk. Current asset and fixed asset investments have a positive effect on market value by signaling confidence in operational performance. Dividend payouts have a positive effect on market value, demonstrating a commitment to returning value to investors, resulting in a stronger firm reputation and investor perception. However, firms that adhere to sustainable development guidelines face more complex dynamics. The results show that both earnings per share and book value per share have a negative effect on market value, suggesting that while they report high earnings per share and book value per share, these financial metrics cannot alleviate investor skepticism regarding sustainability as a cost of the firm. Short-term debt financing has a positive effect on market value because it provides a flexible and efficient way to fund sustainable investments without diluting equity or incurring long-term debt obligations, while the implications of long-term debt financing and current asset investments are insignificant. Furthermore, the significant positive effect of fixed asset investment underscores the potential long-term benefits of sustainability, despite high initial costs. Lastly, the non-significant negative impact of dividend payouts on market value suggests that the overall effect may also depend on various factors. These results support the idea of efficient market theory, which posits that investors may have negative reactions to what they perceive as financial burdens, diminishing the importance of positive financial metrics and altering market value. This study recommends that policymakers should carefully design regulations and incentives to support sustainable investments. Such approaches may include establishing specific funds, tax incentives, subsidies, and soft loans. Additionally, policymakers need to promote transparency and consistent reporting on the long-term financial benefits of sustainability, which can help reduce investor skepticism and foster a more positive market response. Finally, firms should clearly communicate their long-term sustainability efforts and benefits to investors and various stakeholders, leading to a positive interpretation of the firm's commitment to sustainable development.